The Market Evaluation of Criminality: Evidence from the Auction of British Convict Labor in America, 1767–1775 - Grubb, Farley (American Economic Review, 2001)
The Market Evaluation of Criminality: Evidence from the Auction of British Convict Labor in America, 1767-1775 by Farley Grubb. Published in volume 91, issue 1, pages 295-304 of American Economic Review, March 2001